PKC Anchoring to GluR4 AMPA Receptor Subunit Modulates PKC-Driven Receptor Phosphorylation and Surface Expression - Gomes, André R. (2007)
Changes in the synaptic content of 03B1-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA)2013type glutamate receptors lead to synaptic efficacy modifications, involved in synaptic plasticity mechanisms believed to underlie learning and memory formation. Early in development, GluR4 is highly expressed in the hippocampus, and GluR4-containing AMPA receptors are inserted into synapses. During synapse maturation, the number of AMPA receptors at the synapse is dynamically regulated, and both addition and removal of receptors from postsynaptic sites occur through regulated mechanisms. GluR4 delivery to synapses in rat hippocampal slices was shown to require protein kinase A (PKA)2013mediated phosphorylation of GluR4 at serine 842 (Ser842). Protein kinase C (PKC) can also phosphorylate Ser842, and we have shown that PKC03B3 can associate with GluR4. Here we show that activation of PKC in retina neurons, or in human embryonic kidney 293 cells cotransfected with GluR4 and PKC03B3, increases GluR4 surface expression and Ser842 phosphorylation. Moreover, mutation of amino acids R821A, K825A and R826A at the GluR4 C-terminal, within the interacting region of GluR4 with PKC03B3, abolishes the interaction between PKC03B3 and GluR4 and prevents the stimulatory effect of PKC03B3 on GluR4 Ser842 phosphorylation and surface expression. These data argue for a role of anchored PKC03B3 in Ser842 phosphorylation and targeting to the plasma membrane. The triple GluR4 mutant is, however, phosphorylated by PKA, and it is targeted to the synapse in CA1 hippocampal neurons in organotypic rat hippocampal slices. The present findings show that the interaction between PKC03B3 and GluR4 is specifically required to assure PKC-driven phosphorylation and surface membrane expression of GluR4.